Establishments dynamics, vacancies and unemployment: A neoclassical synthesis - Marcelo Veracierto (Federal Reserve Bank of Chicago, 2009)
This paper develops a Walrasian equilibrium theory of establishment dynamics and matching frictions and uses it to analyze business cycle fluctuations. Two scenarios are considered: one in which the matching process is subject to congestion externalities and another in which it is not. The paper finds that the scenario with congestion externalities replicates U.S. business cycle dynamics much better than the scenario with efficient matching. Reallocation shocks improve the empirical behavior of the model in terms of microeconomic adjustments but have little consequences for aggregate dynamics.
Keywords: 330